Uji Fitokimia dan Formulasi Sediaan Salep Ekstrak Etanol Daun Mangkokan (Nothoponax scutellarium Merr.) - Ibrahim, Marisa Anggia; Mewar, Djulfikri; Mahulauw, Muhammad Azril Hardiman (JUKEJ : Jurnal Kesehatan Jompa, 2025)
Mangkokan leaf (Nothopanax scutellarium Merr.) is a potential medicinal plant that contains various active compounds such as alkaloids, flavonoids, saponins, and tannins that are efficacious as antibacterial, anti-inflammatory, and accelerate wound healing. This study aims to formulate mangkokan leaf extract into ointment preparations and evaluate its physical quality. The research method used a laboratory experimental approach with a series of quality tests including organoleptic, homogeneity, pH, spreadability and adhesion. The results of phytochemical testing showed the presence of secondary metabolite compounds, namely alkaloids, flavonoids, saponins and tannins, the results of physical evaluation that the three ointment formulas met all test parameters: having sTabel organoleptic properties, homogeneous texture, pH 4.5-7.0 which is suiTabel for the skin, optimal spreadability of 5-7 cm, adhesion of more than 4 seconds. These findings prove that mangkokan leaf extract can be formulated into ointment preparations that meet the quality standards of topical preparations with the best performance at 30% concentration. This study also confirmed the potential of mangkokan leaves as an effective traditional medicine raw material for wound care and other skin problems, with the advantage of good formula stability during the observation period.